Characterization of The Heat Transfer on Spray Quenching for Different Material Properties - S Sabariman; E. Specht (Atom Indonesia, 2021)
A broad range of water spray applications as a means of two-phase cooling scheme has encouraged researches in the thermal management system to support safety and process efficiency in industries. In the application of above saturation temperature, the cooling process follows the boiling curve where the dissipated heat flux is figured out as a function of the wall temperature. Knowledge on constructing the boiling curve is an essential part in order to define the moving boundary, and boundary value problems occur in metal cooling process analysis involving heat transfer and phase change. The objective of the research was to characterize the boiling parameters on different materials in the regime of film boiling, transition boiling, and nucleate boiling as the basis for its boiling curve construction. To explain the influence of material properties, this work is featuring, firstly, the calculated vapor film thickness in film boiling regime by promoting self-developed analytical model of single droplet and, secondly, the calculated boiling width which indicates a strong combination of surface temperature and heat flux observed as the boiling phenomena. This is obtained by calculating the propagation of wetting front and 100 oC points. This experimental work employed a volumetric spray flux of 4.2, 10 and 13.7 kg/m2s to cool a hot metal samples of aluminum alloy AA6082 and nickel heated up to 560 °C. An infrared camera was used to record the temperature drop over time. Heat flux calculation follows the numerical procedure according to 1D energy balance model. Calculated vapor film thickness explains why the HTC tends to increase with the decrease of the surface temperature. Leidenfrost and Departure from Nucleate Boiling (DNB) temperatures are found to be inversely proportional to the heat penetration coefficient of the metal while maximum heat flux and boiling width increase with it.